2004
DOI: 10.1038/nm1163
|View full text |Cite|
|
Sign up to set email alerts
|

The clock gene Per2 influences the glutamatergic system and modulates alcohol consumption

Abstract: NM A22834 (Albrecht) 3 Across a spectrum of living organisms, ranging from cyanobacteria to humans, it has been observed that biological functions follow a pattern of circadian rhythmicity.These endogenous rhythms display a periodicity close to 24 hours in the absence of environmental cues, thus reflecting the existence of an intrinsic biological clock. In mammals, circadian rhythms in different tissues are coordinated by a master clock located in the suprachiasmatic nucleus (SCN) of the anterior hypothalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
525
8
10

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 531 publications
(571 citation statements)
references
References 45 publications
28
525
8
10
Order By: Relevance
“…Our key finding is that this phenomenon is mediated by the CNS and the clock gene mPer2, and not by circadian variations in ethanol metabolism. These findings might well be translated to the human level, as we could repeatedly demonstrate in previous studies that variations in the human Per2 gene are associated with high alcohol consumption (Spanagel 2009)--an observation, which is in accordance with enhanced alcohol consumption in Per2 Brdm1 mutant mice (Spanagel et al 2005a). High doses of ethanol induce LORR.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our key finding is that this phenomenon is mediated by the CNS and the clock gene mPer2, and not by circadian variations in ethanol metabolism. These findings might well be translated to the human level, as we could repeatedly demonstrate in previous studies that variations in the human Per2 gene are associated with high alcohol consumption (Spanagel 2009)--an observation, which is in accordance with enhanced alcohol consumption in Per2 Brdm1 mutant mice (Spanagel et al 2005a). High doses of ethanol induce LORR.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, we were able to demonstrate that mutations in Per1 and Per2 genes can modulate the effects of drugs of abuse in a different manner (Abarca, Albrecht & Spanagel 2002;Spanagel et al 2005aSpanagel et al , 2005bZghoul et al 2007;Perreau-Lenz & Spanagel 2008;Spanagel 2009). In particular, we established that although mice mutant in the Per2 gene (Per2 Brdm1 ) display enhanced alcohol consumption and preference (Spanagel et al 2005a), Per1 Brdm1 mutant mice did not show such an enhancement in alcohol drinking behavior (Zghoul et al 2007). Hence, in order to more closely elucidate the role of the circadian clock in ethanol's effects on brain sensitivity, we therefore examined the diurnal rhythm of CNS sensitivity in the mouse clock mutants Per1 Brdm1 and Per2 Brdm1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a SNP in BMAL1 and a SNP in the Timeless gene have also been identified that associate with BPD (Mansour et al, 2006). It should be noted that additional studies have found associations between members of the molecular clock and other psychiatric disorders such as schizophrenia and alcoholism, suggesting that these genes are important in a range of psychiatric conditions (Spanagel et al, 2005;Mansour et al, 2006). However, in general, most of these studies only find modest associations, and other studies that have examined SNPs throughout the sequence of some of the central members of the circadian clock have found no associations with these genes and any psychiatric disorders (Shiino et al, 2003;Nievergelt et al, 2005;Mansour et al, 2006;Nievergelt et al, 2006).…”
Section: Human Genetic Studiesmentioning
confidence: 99%
“…This hyperglutamatergic state may then drive alcohol-seeking and relapse behavior (Tsai et al 1995;Spanagel and Kiefer 2008). Acamprosate dampens hyperglutamatergic activity in excessively ethanol drinking mice, thereby reducing alcohol intake (Mann et al 2008;Spanagel et al, 2005). In a recent double-blind, placebo-controlled study, which applied magnetic resonance spectroscopy acamprosate also reduced glutamate levels in the brains of detoxified alcoholdependent patients (Umhau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%